СEMENT CONCRETE ROAD COVERINGS AND THEIR CRACK RESISTANCE - J. G. Babaskin; I. I. Leonovich (Наука и техника)
Crack formation in сement concrete is due to structural and adhesive processes occurring under influence of temperature, water and corrosion factors. The paper proposes methods for protection of сement concrete plates by an organic material or a cement concrete protection layer which is separated from a basic plate by an elastic membrane.